Strategy first: Ten questions to answer before starting an international campus - Jana M. Kleibert; Tim Rottleb; Marc Schulze; Alice Bobée (Leibniz-Institut für Raumbezogene Sozialforschung (IRS), 2021)
The report is intended for senior managers and decision-makers of internationalisation strategies at higher education institutions around the world, and organisations that are involved in consulting, advertisement and support of the internationalisation of higher education. Based upon 136 qualitative interviews with senior higher-education managers and transnational education stakeholders in Europe, Asia and the Middle East conducted between 2018 and 2020, we develop recommendations for developing strategies and avoiding risks in offshore campus development. The report: (1) Discusses the key challenges for international campus developments. It reveals lessons to be learned from failures. (2) Systematically discusses the six most common risks for offshore campuses; including a lack of institutional strategy, financial and reputational risks as well as risks relating to peripheral locations, risky partnerships, and changing regulations in host environments. (3) Develops risk mitigation strategies on the basis of a ten-question checklist.
Keywords: 370; Hochschule; Globalisierung; Risikomanagement; Strategie; Befragung; Europa; Asien; Mittlerer Osten